Some Durability Test of No-Fine Concrete (Journal of Engineering, 2016)
In this study, two types of mixes were adopted by using two grading of coarse aggregate. The practical side of this study was to produce no-fine aggregate concrete by using crushed clay brick aggregates. The durability of the produced concrete and internal sulfate attack was studied.      For durability assessment, it is found that the no-fine concrete made with crushed brick aggregate lost about (15-25) % of its compressive strength after being subjected to 60 cycles of wetting and drying with age 120 days. The curing condition showed that the water curing improved the compressive strength with a rate higher than that when sealed or air dry curing were used. The crushed brick no-fine concrete deteriorated in compressive strength after exposure to internal sulfate attack for 60 cycles; the percentage decrease was about (23.33-25) and (25-27.5) % for 0.57 and 0.83sulfate content respectively.